1968
DOI: 10.1126/science.159.3810.114
|View full text |Cite
|
Sign up to set email alerts
|

Littorina littorea : Occurrence in a Northern Newfoundland Beach Terrace, Predating Norse Settlements

Abstract: in which are found mainly norepinephrine-containing nerve endings and axons is due to a change in some regulatory mechanism acting upon the uptake process. This effect seems to be specific for norepinephrine; we have not been able to detect it with H3-serotonin under similar experimental conditions (8).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…' Clarke (1971) concluded that post-Pleistocene L. littorea arrived from Europe on driftwood that ''would have had to travel from Europe south to North Africa, across the Atlantic in the Equatorial Drift, and north in the Gulf Stream'' (we note that this is an improbable survival route for a cold-water snail). Bird (1968) and Reid (1996) also suggested that North American ancient L. littorea could represent chance arrivals of drifted adults. However, Clarke (1971) also suggested that a native North American L. littorea population could have gone extinct prior to European contact, and the present-day population was introduced by humans through transport from Europe by ships.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…' Clarke (1971) concluded that post-Pleistocene L. littorea arrived from Europe on driftwood that ''would have had to travel from Europe south to North Africa, across the Atlantic in the Equatorial Drift, and north in the Gulf Stream'' (we note that this is an improbable survival route for a cold-water snail). Bird (1968) and Reid (1996) also suggested that North American ancient L. littorea could represent chance arrivals of drifted adults. However, Clarke (1971) also suggested that a native North American L. littorea population could have gone extinct prior to European contact, and the present-day population was introduced by humans through transport from Europe by ships.…”
Section: Introductionmentioning
confidence: 93%
“…From the trench walls were obtained two examples of L. littorea and one specimen of Buccinum undatum Linne.' ' Bird (1968) noted that the specimens lay ''several feet below the surface, clearly in the undisturbed, wave-deposited material'' and therefore ''date from the period of terrace formation.'' All three of Bird's (1968) ''wave deposited'' species were also human food species.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The species was found in several post-Pleistocene archaeological sites in New Brunswick and Nova Scotia (Clarke, 1963). Bird (1968) recorded L. littorea from pre-Viking strata in N ewfoundland, and Wagner (1977) found a single specimen in sediments dated at 40,000 years B.P. in Nova Scotia.…”
Section: Historical Backgroundmentioning
confidence: 99%